Islamic Monetary Management: A Critical Overview - Qudsi Fauzi, R M; Indri Hapsari, M (KnE Social Sciences, 2019)
The paper aims to provide critical overview of Islamic monetary management. This is literature study based on secondary data taken from some books, articles, and journal discussed related to modern monetary economic and Islamic monetary economic. The references were produced by some authors who are concern in the area of monetary system and monetary policy. The rest of this paper is structured as follow: Section 1 gives an overview of background and monetary policy frameworks where Islamic banks operate; Section 2 explores the monetary management in modern economy; Section 3 gives information about the objective of monetary management; section 4 discusses the monetary policy operational framework for Islamic banks; and Section 5 explains Islamic monetary instrument; meanwhile Section 6 gives a critical overview; and Section 7 is conclusion. Keywords: Monetary management, Islamic Monetary management